1992
DOI: 10.1111/j.1464-5491.1992.tb01819.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems with Gait and Posture in Neuropathic Patients with Insulin‐Dependent Diabetes Mellitus

Abstract: Peripheral neuropathy secondary to diabetes mellitus is believed to cause postural instability and uncoordinated gait, although this is not well documented. Two groups of patients from the Pittsburgh Epidemiology of Diabetes Complications Study, matched for age and duration of Type 1 diabetes, but with significantly different vibratory sensation thresholds as determined by Vibratron II testing, were therefore surveyed. The mean ages were 32.9 and 31.9 years and durations of diabetes were 22.0 and 18.8 years fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
172
1
7

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(185 citation statements)
references
References 15 publications
5
172
1
7
Order By: Relevance
“…Subjects with diabetic peripheral neuropathy are 23 times more likely to fall (7) and are 15 times more likely to report an injury compared to matched non-neuropathic subjects (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects with diabetic peripheral neuropathy are 23 times more likely to fall (7) and are 15 times more likely to report an injury compared to matched non-neuropathic subjects (1).…”
Section: Introductionmentioning
confidence: 99%
“…Lower limb diabetic sensory neuropathy has an adverse effect on postural stability and walking (1) and ultimately increases the risk of falling in people with diabetes. Subjects with diabetic peripheral neuropathy are 23 times more likely to fall (7) and are 15 times more likely to report an injury compared to matched non-neuropathic subjects (1).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous human studies report that patients with DPN are at increased risk for falls due to decreased postural control, altered gait and balance, and increased body sway (7)(8)(9). The underlying neurologic mechanisms involved in large-fiber DPN remain poorly understood.…”
mentioning
confidence: 99%
“…Future studies should include patients with conditions that can affect their gait such as diabetes [39], Parkinson's [40] or patients with Multiple Sclerosis (MS) disease [41]. Several studies have also confirmed a relationship between gait variability and age progression [42][43][44].…”
Section: Future Workmentioning
confidence: 99%